Quantification of the components of resistance to rice sheath blight using a detached tiller test under controlled conditions - Willocquet, Laetitia; Lore, Jagjeet S.; Srinivasachary, S.; Savary, Serge (Scientific Societies, 2011)
Resistance of rice (Oryza sativa) to sheath blight, caused by Rhizoctonia solani, is quantitative and involves two mechanisms: physiological resistance and disease escape. The epidemiological concept of components of resistance was applied using a detached tiller method under controlled conditions, to specifically address physiological resistance to sheath blight in rice. A sclerotium was inserted below the leaf collar of individual rice tillers maintained in tubes filled with water. Different variables were measured after incubation: number of lesions, lesion length, vertical sheath colonization, presence or absence of dark margin at the edge of lesions, and survival duration of the leaf blade. Several rice varieties reported to have different levels of susceptibility to sheath blight were assessed, together with varieties that are cultivated over large areas. Although numerical differences between rice varieties were observed for all disease variables, only the number of lesions significantly differed among varieties tested in this study. The varieties Pecos and IR64 had the consistently lowest and highest disease intensities, respectively. This methodology may allow the detection of sources of resistance that specifically involve defense mechanisms. When combined with field assessment, this methodology should also enable to quantitatively assess the relative role of both mechanisms of resistance to sheath blight.